Personnel management: human relations in industry - Deverell, Cyril S. (London : Gee & Co., 1968)
This book is an introduction. It cannot include everything about human relations. It runs alongside the study of industrial relations and from time to time gets entangled with it. The interactions between individuals and organization structure bring it into theories of organization.
Includes index.
Includes bibliographical references p. 257-259
hza 18/07/2018
Loan
Keywords: Personnel management